Spatial–temporal distribution measurement of input–output efficiency of the water–energy–food nexus of the Yangtze River Economic Belt, China - Ni, Yikun; Chen, Yan (Frontiers in Ecology and Evolution, 2022)
Water resources, energy, and food are important factors affecting people's life and socioeconomic development, which makes it necessary to take them as a whole to do research. The analysis of the spatial-temporal distribution of the input-output efficiency of the WEF(Water-Energy-Food) nexus is conducive to the effective utilization and rational distribution of relevant resources in the Yangtze River Economic Belt. This paper constructs an index system by selecting the consumption of the water resources, energy, and food as input variables, gross domestic product as expected output variable, and waste gas, waste water, and general industrial solid waste as unexpected output variables. Then the input-output efficiency of the nexus of 11 provinces and cities in the Yangtze River Economic Belt from 2011 to 2019 was calculated. After that, using the DEA-BCC and standard deviational ellipse models, two new indictors which called WEF nexus’s efficiency area expansion degree and the subsystem’s influence degree on the transfer of nexus’s center of gravity are put forward, and the characteristics and trend of time evolution and spatial distribution of input-output efficiency of the WEF nexus are quantitatively identified. The results show that (1) the efficiency of the eastern coastal areas is high than that of the western inland areas, and the efficiency of the middle-lower reaches is higher than that of the upper reaches. (2) The center of gravity of efficiency is located in the middle reaches and shows a trend of transfer from southwest to northeast. (3) The difference of input-output efficiency between provinces and cities inside and outside the ellipse was the largest in 2018. (4) The water resources subsystem has the greatest impact on the transfer of the center of gravity of the WEF nexus. The paper uses two models and two indictors to analyze distribution characteristics and trend of input-output efficiency of the WEF nexus of the Yangtze River Economic Belt from the perspective of time and space and puts forward the corresponding policy recommendations according to the different characteristics of middle-lower reaches and upper reaches respectively, which provides a scientific reference for related resources strategy of the Yangtze River Economic Belt.